A Nonthoracotomy Myocardial Infarction Model in an Ovine Using Autologous Platelets. (3rd December 2013) - Spata, Tyler; Bobek, Daniel; Whitson, Bryan A.; Parthasarathy, Sampath; Mohler, Peter J.; Higgins, Robert S. D.; Kilic, Ahmet
Abstract : Objective . There is a paucity of a biological large animal model of myocardial infarction (MI). We hypothesized that, using autologous-aggregated platelets, we could create an ovine model that was reproducible and more closely mimicked the pathophysiology of MI. Methods . Mepacrine stained autologous platelets from male sheep (n = 7 ) were used to create a myocardial infarction via catheter injection into the mid-left anterior descending (LAD) coronary artery. Serial daily serum troponin measurements were taken and tissue harvested on post-embolization day three. Immunofluorescence microscopy was used to detect the mepacrine-stained platelet-induced thrombus, and histology performed to identify three distinct myocardial (infarct, peri-ischemic "border zone, " and remote) zones. Results . Serial serum troponin levels ( μ g/mL) measured 0.0 ± 0.0 at baseline and peaked at 297.4 ± 58.0 on post-embolization day 1, followed by 153.0 ± 38.8 on day 2 and 76.7 ± 19.8 on day 3. Staining confirmed distinct myocardial regions of inflammation and fibrosis as well as mepacrine-stained platelets as the cause of intravascular thrombosis. Conclusion . We report a reproducible, unique model of a biological myocardial infarction in a large animal model. This technique can be used to study acute, regional myocardial changes following a thrombotic injury.